Report of the Janapada Enquiry Committee Madhya Pradesh 1952 - Planning Commission (Planning Commission, 1952)
The State Government have been considering the necessity of examining the question of Janapada finances and problems, and administrative and other difficulties of the Janapada Sabhas. There has been a complaint that Janapada Sabhas have not been able to discharge properly the numerous and important functions devolving on them because their financial resources are slender. There also has been a constant criticism that all the executive powers have been vested in the Chief Executive Officer, and the non-officials do not take a more lively interest in the working of the Janapada Sabhas.
Government of Madhya Pradesh
Government of Madhya Pradesh